Deskripsi Pembelajaran Membaca pada Siswa Kelas I Sekolah Dasar Negeri 14 Darok - Kiki Arianti; Antonius Totok Priyadi; Hairida Hairida (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study aims to describe what is meant by learning to read, describe what factors cause first grade students to have difficulty reading, describe how teachers overcome difficulties in early reading in first grade students. The method used is a qualitative descriptive method. This study uses test instruments, observations, and interviews. The results of the study are as follows: difficulty reading one word pictures, not being able to recognize and pronounce the letters of the alphabet, difficulty distinguishing almost the same letters, not being able to spell, difficulty reading one open syllable, reading haltingly, quickly forgetting the words they spell and spelling for a long time, the factors causing early reading difficulties in first grade students of State Elementary School 14 Darok can be seen from two different factors, namely internal factors and external factors. Internal factors are factors that come from the students themselves, namely interest factors and motivation factors. While external factors come from parents and teachers to students. Factors originating from parents are lack of attention and support to children at home, actions taken by teachers in overcoming or handling students who experience early reading difficulties are by calling students repeatedly every day and then teaching them to read. Meanwhile, teacher factors include ineffective classroom management.